196k views
5 votes
???????????????????????????????????

???????????????????????????????????-example-1
User Bluedaniel
by
5.6k points

2 Answers

3 votes

The answer is 33p + 58x


To get the answer you need to simplify the parenthesis first, so 11*3p = 33p + 11*5x = 55x


Now we have 33p+55x then we take down 33p+55x+4x-x


55x+4x = 59x bring down, 33p+59x-x


59x-x = 58x, bring down

33p + 58x = 11(3p+5x)+4x-x simplified

User Lombo
by
5.5k points
1 vote
the answer is 33p+58x
User Kenesha
by
5.6k points